The surgical pain in surgical squad in opinion of questionnaire study with use of questionnaire the McGill-Melzack - preliminary report - Kołodziej, Wiesława; Karpel, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. In course of development of medical sciences the felt by ill after operating intervention pain be perceived as the patients’ basic problem. With information, what patient will get should to result, that more easily is prevent pain she than fight already appears and skill help straight lines the scales of opinion of pain should be used in this process. Analgesic treatment should be diverse, individualized and contain component anxiety against. The aim. The analysis of kind is the aim of work and the degree of felt pain in direct surgical period on basis of sectional epidemiological investigation from utilization the questionnaire the McGill-the Melzack as well as opinion of his usefulness in practice the surgical conduct in surgery. Material and method. The investigation was conducted at 132 ill operated in data period of time in two chosen the hospitals on terrain of Silesian province. It the investigation of surgical pain at operated ill was based was about questionnaire McGill-Melzack (MPQ). Results and conclusions. The questionnaire the McGill-the Melzack the state useful, though the difficult tool of investigation of pain in surgical period. Pain permits to differentiate felt in sphere sensory and affective. The difference of level of pain in T2 in relation to T1 contains in compartment 1 point on scale of pain. Women more strongly feel pain. In they fighting pain they be applied traditional methods.